How Do MNCS Vote in Developing Country Elections? - Vaaler, Paul M. (Academy of Management Journal, 2008)
Research on multinational corporations (MNCS) and host government political risk in developing countries has largely ignored local electoral politics, economic policies, and the MNC investment incentives they may generate. In response, I develop and test a framework for understanding MNC risk and investment behavior based on political business cycle considerations. Analyses of 408 MNC investments worth $199 billion in 18 developing countries holding 35 presidential elections from 1987 through 2000 are consistent with these considerations: MNCS perceive higher (lower) risk and announce fewer (more) investment projects as right-wing (left-wing) incumbents appear more likely to be replaced by left-wing (right-wing) challengers.